Human Papillomavirus (HPV) Awareness, HPV-Related Concern, and Fear of Cancer as Predictors of Attitudes Toward Cervical Cancer Prevention in Women - Cirban Ekrem, Ebru; Temiz, Mehtap (Wiley, 2026)
Aim This study examines the associations of human papillomavirus awareness, HPV-related concern, and fear of cancer with women's attitudes toward preventing cervical cancer (CC). Method This cross-sectional, correlational study was conducted with women aged 18-65 years who attended a community health center in a province in northwestern Turkiye. Participants were recruited from women presenting to the Bart & imath;n Community Health Center for various health services (e.g., examination, screening, or accompaniment). The study was completed with 640 women who met the inclusion criteria. Data were collected using the Descriptive Information Form, the Human Papillomavirus Awareness and Concern Scale (HPV-ACS), the Fear of Cancer Scale (FCS), and the Attitude Scale for Protection From Cervical Cancer (ASPFCC). Results HPV-ACS, FCS, and ASPFCC scores were significantly associated with women's sociodemographic characteristics (p < 0.05). When factors associated with ASPFCC were examined, the independent variables explained 11% of the variance in attitudes toward preventing CC. Women's attitudes toward preventing CC were significantly associated with age (B = 0.440, p < 0.001), HPV-ACS scores (B = 0.294, p < 0.001), and fear of cancer (B = 0.228, p < 0.001). Conclusion In this study, women's HPV awareness and HPV-related concern levels and their attitudes toward preventing CC were high, while fear of cancer was at a moderate level. Higher HPV awareness, HPV-related concern, and fear of cancer were associated with more positive attitudes toward preventing CC.
Keywords: Cervical Cancer; Fear Of Cancer; Hpv Awareness; Hpv-Related Concern; Women